Tire pyrolysis oil in Brazil: Potential production and quality of fuel - Gamboa, Alexander R. [UNESP]; Rocha, Ana M.A.; dos Santos, Leila R.; de Carvalho, João A. [UNESP] (Elsevier, 2020)
The application of tire pyrolysis technology in a country will be feasible whenever competitive and attractive products are produced. In this work, quantitative and qualitative evaluation of the potential of tire pyrolysis oil (TPO) in Brazil was carried out. The quantitative evaluation consisted of determining the amount of feedstock (waste tires) available and the volume of TPO that can be produced in Brazil per year. The qualitative evaluation was applied to a sample of TPO produced in Brazil, determining its main atomization properties: specific mass, viscosity and surface tension. In addition, a theoretical comparison of the quality of TPO spray was performed, comparing the expected mass median diameter for TPO and diesel oil (DO) spray. The results of the quantitative evaluation showed that it is possible to produce around 230 to 280 thousand m³ per year of TPO, equivalent to about 2% of the onshore petroleum and fuel oil (FO) produced in Brazil for both cases. Meanwhile, the qualitative evaluation showed that the TPO produced in Brazil has greater ease of atomization in relation to the FO produced and marketed in the country. However, preserving the quality of TPO requires proper storage, since prolonged exposure to the environment increases its viscosity by up to four times, and can change it from medium oil (22.3oAPI) to heavy oil (14.1oAPI).
Keywords: Brazil; Potential production; Pyrolysis; Tire pyrolysis oil; Waste tires